Synthesis of Ni doped barium hexaferrite by microemulsion route to enhance the visible light-driven photocatalytic degradation of crystal violet dye. Issue 3 (1st February 2023) - Muhiuddin, Ghulam; Bibi, Ismat; Nazeer, Zarish; Majid, Farzana; Kamal, Shagufta; Kausar, Abida; Raza, Qasim; Alwadai, Norah; Ezzine, Safa; Iqbal, Munawar
Abstract: The pristine and Ni doped BaNix Fe12-x O19 (x = 0.0, 0.2, 0.4, 0.6, 0.8, 1.0) NPs have been fabricated via facile microemulsion approach and the impact of dopants was explored based dielectric, optical, structural and the photocatalytic properties of BaNix Fe12-x O19 nanoparticles. X-ray diffraction and Raman study confirmed the formation of regular hexagonal geometry with space group P63 /mmc with crystallite size in 32–50 nm range. Functional groups were identified using FTIR analysis. The remanence (Pr), saturation polarization (Ps) and coercivity (Hc) was explored by P-E loop analysis and the value of Pr and Ps was enhanced with the concentration of dopant. According to PL spectra, highly doped materials had a higher charge separation (e − - h + ) and low recombination rate, which resulted in higher photocatalytic degradation activity of fabricated nanomaterials. The optical band gap was found to be 1.78 eV versus undoped (2.60 eV for pristine BaFe12 O19 ). Due to polarizations, the dielectric loss, dielectric constant and tangent loss values were declined, while AC conductivity was enhanced. Photocatalytic performance of doped and undoped samples under visible right irradiation was studied for crystal violet dye. For 100 min exposure to visible light, the highly doped catalyst exhibits 97% degradation versus 60% in case of pristine this is attributed to efficient electron-hole pair separation. Furthermore, quenching effect of different scavengers indicated that hydroxyl radical had a main role, and e − or h + played a minimal role in CV dye degradation. The enhanced properties due to doping make BaNix Fe12-x O19 a potential candidate for photocatalytic applications under visible light irradiation.